Business Information Systems 13th International Conference, BIS 2010, Berlin, Germany, May 3-5, 2010. Proceedings - Abramowicz, Witold; Tolksdorf, Robert; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book contains the refereed proceedings of the 13th International Conference on Business Information Systems, BIS 2010, held in Berlin, Germany, in May 2010. The 25 revised full papers were carefully reviewed and selected from more than 80 submissions. Following the theme of the conference "Future Internet Business Services", the contributions detail recent research results and experiences and were grouped in eight sections on search and knowledge sharing, data and information security, Web experience modeling, business processes and rules, services and repositories, data mining for processes, visualization in business process management, and enterprise resource planning and supply chain management.
Session 1. Search and Knowledge Sharing -- Faceted Wikipedia Search -- A Model of Cross-Functional Coopetition in Software Development Project Teams -- Using Probabilistic Topic Models in Enterprise Social Software -- Session 2. Data and Information Security -- Using SPARQL and SPIN for Data Quality Management on the Semantic Web -- Quality in Blogs: How to Find the Best User Generated Content -- Avoiding Inconsistency in User Preferences for Data Quality Aware Queries -- Session 3. Web Experience Modelling -- Textractor: A Framework for Extracting Relevant Domain Concepts from Irregular Corporate Textual Datasets -- Comparing Intended and Real Usage in Web Portal: Temporal Logic and Data Mining -- Capturing Eye Tracking Data for Customer Profiling -- Session 4. Business Processes and Rules -- Consistency Checking of Compliance Rules -- From Economic Drivers to B2B Process Models: A Mapping from REA to UMM -- Using Surveys to Evaluate a Business Rules Based Development Approach -- Session 5. Services and Repositories -- Identification of Services through Functional Decomposition of Business Processes -- Requirements for a Business Process Model Repository: A Stakeholders$1 (BPerspective -- Supporting Complex Business Information Systems -- Session 6. Data Mining for Processes -- On Integrating Data Mining into Business Processes -- From Process Execution towards a Business Process Intelligence -- Auditing Workflow Executions against Dataflow Policies -- Workflow Data Footprints -- Session 7. Visualisation in BPM -- On the Cognitive Effectiveness of Routing Symbols in Process Modeling Languages -- Visualising Business Capabilities in the Context of Business Analysis -- A Model Driven Engineering Approach for Modelling Versions of Business Processes using BPMN -- Session 8. ERP and SCM -- Value Propositions in Service Oriented Business Models for ERP: Case Studies -- Event-Driven Business Intelligence Architecture for Real-Time Process Execution in Supply Chains -- Production Inventory and Enterprise System Implementation: An Ex-ante No-Cost Based Evaluation.s
Keywords: Computer science; Information systems; Business logistics; Management information systems; Computer Science; Computer Appl. in Administrative Data Processing; Business Information Systems; Information Systems Applications (incl.Internet).; Production/Logistics.